Perancangan Sistem Informasi E-Learning Berbasis Web Studi Kasus SMK Mandiri - Anna Anna; Raja Sabaruddin; Fitri Fitri (LPPM Universitas Bina Sarana Informatika, 2021)
The effects of the pandemic have resulted in students being required to understand online learning. Many digital media are used by schools to carry out teaching and learning activities, one of which is E- Learning. E-Learning offers an optimal learning process that suits every student's needs and can be accessed anywhere as long as it is connected to an internet connection. The purpose of this research is to produce an E-Learning information system as a means of supporting teaching and learning activities. The model used in building the E- Learning system is the SDLC Waterfall model. The Waterfall method starts from the planning, analysis, design, testing, and maintenance processes on the system. Web-based e-learning is expected to make it easier for teachers to provide materials, assignments, and exams online through the website. Likewise, students can also access E- Learning materials anytime and anywhere using various types of gadgets they have.